Salinity-Mediated Increment in Sulfate Reduction, Biofilm Formation, and Quorum Sensing: A Potential Connection Between Quorum Sensing and Sulfate Reduction? - Sivakumar, Krishnakumar; Scarascia, Giantommaso; Zaouri, Noor; Wang, Tiannyu; Kaksonen, Anna H.; Hong, Pei-Ying (Frontiers in Microbiology, 2019)
Biocorrosion in marine environment is often associated with biofilms of sulfate reducing bacteria (SRB). However, not much information is available on the mechanism underlying exacerbated rates of SRB-mediated biocorrosion under saline conditions. Using Desulfovibrio (D.) vulgaris and Desulfobacterium (Db.) corrodens as model SRBs, the enhancement effects of salinity on sulfate reduction, N-acyl homoserine lactone (AHL) production and biofilm formation by SRBs were demonstrated. Under saline conditions, D. vulgaris and Db. corrodens exhibited significantly higher specific sulfate reduction and specific AHL production rates as well as elevated rates of biofilm formation compared to freshwater medium. Salinity-induced enhancement traits were also confirmed at transcript level through reverse transcription quantitative polymerase chain reaction (RT-qPCR) approach, which showed salinity-influenced increase in the expression of genes associated with carbon metabolism, sulfate reduction, biofilm formation and histidine kinase signal transduction. In addition, by deploying quorum sensing (QS) inhibitors, a potential connection between sulfate reduction and AHL production under saline conditions was demonstrated, which is most significant during early stages of sulfate metabolism. The findings collectively revealed the interconnection between QS, sulfate reduction and biofilm formation among SRBs, and implied the potential of deploying quorum quenching approaches to control SRB-based biocorrosion in saline conditions.